Glioma‐Associated Stem Cells: A Novel Class of Tumor‐Supporting Cells Able to Predict Prognosis of Human Low‐Grade Gliomas. (17th April 2014) - Bourkoula, Evgenia; Mangoni, Damiano; Ius, Tamara; Pucer, Anja; Isola, Miriam; Musiello, Daniela; Marzinotto, Stefania; Toffoletto, Barbara; Sorrentino, Marisa; Palma, Anita; Caponnetto, Federica; Gregoraci, Giorgia; et al.
Abstract: Background : Translational medicine aims at transferring advances in basic science research into new approaches for diagnosis and treatment of diseases. Low‐grade gliomas (LGG) have a heterogeneous clinical behavior that can be only partially predicted employing current state‐of‐the‐art markers, hindering the decision‐making process. To deepen our comprehension on tumor heterogeneity, we dissected the mechanism of interaction between tumor cells and relevant components of the neoplastic environment, isolating, from LGG and high‐grade gliomas (HGG), proliferating stem cell lines from both the glioma stroma and, where possible, the neoplasm. Methods and Findings : We isolated glioma‐associated stem cells (GASC) from LGG (n=40) and HGG (n=73). GASC showed stem cell features, anchorage‐independent growth, and supported the malignant properties of both A172 cells and human glioma‐stem cells, mainly through the release of exosomes. Finally, starting from GASC obtained from HGG (n=13) and LGG (n=12) we defined a score, based on the expression of 9 GASC surface markers, whose prognostic value was assayed on 40 subsequent LGG‐patients. At the multivariate Cox analysis, the GASC‐based score was the only independent predictor of overall survival and malignant progression free‐survival. Conclusions : The microenvironment of both LGG and HGG hosts non‐tumorigenic multipotent stem cells that can increase in vitro the biological aggressiveness of glioma‐initiating cells through the release of exosomes. The clinical importance of this finding is supported by the strong prognostic value associated with the characteristics of GASC. This patient‐based approach can provide a groundbreaking method to predict prognosis and to exploit novel strategies that target the tumor stroma. Stem Cells 2014;32:1239–1253